2007
DOI: 10.1148/radiol.2433060068
|View full text |Cite
|
Sign up to set email alerts
|

Localizing and Lateralizing Language in Patients with Brain Tumors: Feasibility of Routine Preoperative Functional MR Imaging in 81 Consecutive Patients1

Abstract: Functional MR imaging proved to be feasible during routine diagnostic neuroimaging for localizing and lateralizing language function preoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(89 citation statements)
references
References 26 publications
3
83
0
3
Order By: Relevance
“…Information from language task fMRI can be used to non-invasively lateralize (Binder et al, 1996;Woermann et al, 2003) and localize (Carpentier et al, 2001;Brannen et al, 2001) language regions in the brain. Language fMRI is also applied to define spatial relationships between brain lesions and language areas for pre-surgical mapping (Stippich et al, 2007). The sensitivity and specificity of language fMRI are major concerns in generating language maps for clinical use (Tharin and Golby, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Information from language task fMRI can be used to non-invasively lateralize (Binder et al, 1996;Woermann et al, 2003) and localize (Carpentier et al, 2001;Brannen et al, 2001) language regions in the brain. Language fMRI is also applied to define spatial relationships between brain lesions and language areas for pre-surgical mapping (Stippich et al, 2007). The sensitivity and specificity of language fMRI are major concerns in generating language maps for clinical use (Tharin and Golby, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…49 Another patient study even reported 100% sensitivity for both Broca and Wernicke regions. 50 However, all these results were achieved with rather low statistical thresholds.…”
Section: Percentage Of Subjects Activating Normally Expected Languagementioning
confidence: 99%
“…Brain tumors, growing in a rigid structure, cause a buildup of intracranial pressure, altering the normal hemodynamic process of hemoglobin oxygenation in surrounding veins. 30,31 Brain tumors may influence BOLD effect by releasing vasoactive substances and/or neurotransmitters. 32 Disease-induced pathology and/or medications may alter psychological factors such as cognition and attention; this change compromises normal execution of tasks and subsequently renders rigid data analysis ineffective.…”
Section: 27mentioning
confidence: 99%